NOMOPHOBIA COUNSELLING AND SCREENING AMONG HIGH SCHOOL STUDENTS IN SIDOARJO: INTEGRASI PENYULUHAN DAN SKRINING NOMOPHOBIA PADA SISWA SEKOLAH MENENGAH ATAS DI SIDOARJO - Nisa Dewanti; Nina Rizka Rohmawati; Widya Nurcahyaningtyas; Nima Eka Nur Rahmania; Riza Irianingtyas; Tamara Nur Budiarti (Faculty of Vocational Studies, Universitas Airlangga, 2026)
Background: Nomophobia is an increasingly common psychosocial problem among teenagers, affecting mental health and daily physical activity. Therefore, educational and screening efforts are needed to increase awareness and early detection of nomophobia in teenagers. Objective: This community service aims to increase teenagers’ knowledge of smartphone use and to conduct a screening for nomophobia levels. Method: Community service was carried out through outreach activities, including lectures and discussions about the dangers of nomophobia among teenagers. Following the educational session, nomophobia levels were screened using the Indonesian version of the Nomophobia Questionnaire (NMP-Q). The activity was held on May 17, 2025, with 107 participants from grades 10 and 11 at a Madrasah Aliyah (Islamic Senior High School) in Sidoarjo. Results: The screening results showed that most teenagers were in the moderate nomophobia category (54.2%). There was an increase in teenagers’ knowledge of the dangers of nomophobia, as indicated by a higher average score (1.98 to 2.64), and the Wilcoxon Signed Rank test showed a significant difference (p<0.001). Conclusion: This activity plays an effective role in supporting promotive and preventive efforts by integrating counselling and screening, and can serve as a basis for planning further interventions to support mental health and the healthy use of digital technology among teenagers.